Spontaneous pregnancy after full recovery from hypopituitarism caused by lymphocytic hypophysitis. (3rd August 2018) - Funazaki, Shunsuke; Yamada, Hodaka; Hara, Kazuo; Ishikawa, San-e
Summary: Lymphocytic hypophysitis (LyH) has been known to be associated with pregnancy. We herein report the case of a 33-year-old woman who underwent vaginal delivery without massive bleeding at 40 weeks of gestation. Because of the presence of headache and terrible fatigue after childbirth, she visited our hospital. Severe hyponatremia (Na, 118 mEq/L) and visual field abnormality was noted upon examination. MRI revealed pituitary enlargement with a swollen pituitary stalk, albeit at low signal intensity. Basal pituitary hormone levels were all reduced and remained low after exogenous administration of hypothalamic-releasing hormones. She was diagnosed with LyH and was started on prednisolone 60 mg/day. A month later, her pituitary function had gradually improved together with a decrease in pituitary enlargement and recovery of her visual field. The dose of prednisolone was gradually reduced and finally withdrawn 27 months later. After prednisolone withdrawal, her pituitary function remained normal despite the absence of any hormonal replacement. A year later, she became pregnant without medication and delivered a second baby without LyH recurrence. Thereafter, her pituitary function has been normal for more than 5 years. Two valuable observations can be highlighted from the case. First, the patient completely recovered from LyH through prompt prednisolone therapy during its initial phase and had almost normal pituitary function. Second, after recovery from LyH, she was able to undergo spontaneous pregnancy and deliver a baby. We believe that reporting incidences of spontaneous pregnancy after complete normalization of pituitary function in patients with LyH is of great significance. Learning points: Females are more affected by LyH than males given its strong association with pregnancy. LyH possesses characteristic findings on pituitary MRI. Glucocorticoid therapy for LyH has been recommended as an effective treatment. A history of previous pregnancies does not increase the risk of developing AH in subsequent pregnancies. Early induction of high-dose prednisolone was therapeutically effective in treating LyH.